Quo Vadis IAIN Sunan Kalijaga (Upaya Membangun Landasan Awal) - Ainurrafiq Dawam (Al-Jami'ah Research Centre, 2003)
As an Institution of an Islamic higher education, until nowadays IAIN Sunan Kalijaga is still consistent with the study of Islam in the literalistic (wahyiyyah) ways. In the mean time, undeniably, society, knowledge and technology have undergone some significant development. The growth of society, knowledge and technology could not be separated from the development of IAIN itself; the development of IAIN should accommodate to the progress of society, knowledge and technology. However, all above remains idealism for IAIN. In other words, the academic doers of IAIN do not master knowledge and technology yet. This paper is trying to elaborate the fundamental principle of the development of IAIN which covers ideology, epistemology, and the paradigm of Islamic education.